МЕТАФОРИЧЕСКИЙ ПЕРЕНОС В СОВРЕМЕННОМ РУССКОМ ПОЛИТИЧЕСКОМ ДИСКУРСЕ (СФЕРА-ИСТОЧНИК «ТЕАТР») - Szymula, Robert (Acta Neophilologica, 2015)
Metaphorical transfer (primary field “Theatre”) is one of the productive ways for creating new meanings of lexical units, used in modern Russian political discourse. The lexical material collected by the author (press articles from 4 Russian newspapers) demonstrates that this phenomenon may be connected with a strong impact on the receiver’s emotions. The analyzed lexical units may create a negative image of the political world in the receiver’s mind. Politicians’ activity is shown as something unserious or even funny, rather than real work for the community.